STABILIZED1 Modulates Pre-mRNA Splicing for Thermotolerance - Kim, Geun-Don (Plant Physiol, 2017)
High-temperature stress often leads to differential RNA splicing, thus accumulating different types and/or amounts of mature mRNAs in eukaryotic cells. However, regulatory mechanisms underlying plant precursor mRNA (pre-mRNA) splicing in the environmental stress conditions remain elusive. Herein, we describe that a U5-snRNP-interacting protein homolog STABILIZED1 (STA1) has pre-mRNA splicing activity for heat-inducible transcripts including HEAT STRESS TRANSCRIPTION FACTORs and various HEAT SHOCK PROTEINs for the establishment of heat stress tolerance in Arabidopsis (Arabidopsis thaliana). Our cell-based splicing reporter assay demonstrated STA1 acts on pre-mRNA splicing for specific subsets of stress-related genes. Cellular reconstitution of heat-inducible transcription cascades supported the view that STA1-dependent pre-mRNA splicing plays a role in DREB2A-dependent HSFA3 expression for heat-responsive gene expression. Further genetic analysis with a loss-of-function mutant sta1-1, STA1-expressing transgenic plants in Col background, and STA1-expressing transgenic plants in the sta1-1 background verified that STA1 is essential in expression of necessary genes including HSFA3 for two-step heat stress tolerance in plants. However, constitutive overexpression of the cDNA version of HSFA3 in the sta1-1 background is unable to execute plant heat stress tolerance in sta1-1. Consistently our global target analysis of STA1 showed that its splicing activity modulates a rather broad range of gene expression in response to heat treatment. The findings of this study reveal that heat-inducible STA1 activity for pre-mRNA splicing serves as a molecular regulatory mechanism underlying the plant stress tolerance to high-temperature stress.